A social exchange theory framework for understanding the job characteristics–job outcomes relationship: the mediating role of psychological contract fulfillment - Birtch, Thomas A.; Chiang, Flora F.T.; Van Esch, Emmy (Taylor & Francis, 2016)
This study integrated the Job Demands-Resources (JD-R) model and concept of psychological contract fulfillment into a social exchange theory process framework to improve our understanding how and when job characteristics interact to influence job outcomes. Using survey data (n = 334), we found evidence to support our hypothesized relationships between job characteristics (job demands and job resources) and job outcomes (job satisfaction and organizational commitment); and the mediating role of psychological contract fulfillment (transactional and relational), such that when job resources (job control and support) were high, the negative effects of high job demands on psychological contract fulfillment were attenuated. Theoretical and managerial implications are discussed.